1992
DOI: 10.1083/jcb.117.2.437
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fibronectin receptor distribution [published erratum appears in J Cell Biol 1992 Jul;118(2):491]

Abstract: Abstract. To determine the role of each intracellular domain of the fibronectin receptor in receptor distribution, chimeric receptors were constructed containing the human interleukin-2 receptor (gp55 subunit) as the extracellular and transmembrane domains, in combination with either the a5 or ß, intracellular domain of the fibronectin receptor as the cytoplasmic domain . These chimeric receptors were transiently expressed in normal fibroblasts, and their localization on the cell surface was determined by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(62 citation statements)
references
References 48 publications
3
59
0
Order By: Relevance
“…Early studies on integrin-dependent cell adhesion and signalling demonstrated that cell ligation to the ECM was accompanied by integrin aggregation, and that this clustering could trigger increased tyrosine phosphorylation of a number of intracellular proteins [22][23][24][25]. Additional work demonstrated that integrin clusters are concentrated in specialized organelles known as focal adhesions, which are also enriched with bundles of actin and associated cytoskeletal proteins, including vinculin, talin, paxillin and tensin [17,26].…”
Section: Fakmentioning
confidence: 99%
“…Early studies on integrin-dependent cell adhesion and signalling demonstrated that cell ligation to the ECM was accompanied by integrin aggregation, and that this clustering could trigger increased tyrosine phosphorylation of a number of intracellular proteins [22][23][24][25]. Additional work demonstrated that integrin clusters are concentrated in specialized organelles known as focal adhesions, which are also enriched with bundles of actin and associated cytoskeletal proteins, including vinculin, talin, paxillin and tensin [17,26].…”
Section: Fakmentioning
confidence: 99%
“…These conformational changes are associated with a dramatic change in the quaternary structure of the integrin, resulting in a switch from a "bent" conformation observed in the crystal structure (37) to an extended one (38) that features a C-terminal separation (39) that would disrupt the TM helical packing proposed here. This disruption could lead to the changes in the intracellular interactions of occupied integrins manifested by focal adhesion targeting and transdominant inhibition (34,40). Furthermore, the work of Li et al (10) shows that isolated integrin ␣ and ␤ TM peptides homooligomerize, a process that could contribute to integrin clustering.…”
Section: Figmentioning
confidence: 99%
“…All cell lines were maintained in culture in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum, glutamine, penicillin, streptomycin (Biological Industries, Beit Ha'emek, Israel), and 1 mM sodium pyruvate (Sigma). Electroporation of these cells with 30 g of DNA for each chimeric IL-2R/cytoplasmic protein construct was performed as described previously at 170 V and 960 microfarads with a Bio-Rad Gene Pulser but without any thymidine block (22). Some transfections were performed using LipofectAMINE Plus (Invitrogen) utilizing standard protocols.…”
Section: Construction Of Chimericmentioning
confidence: 99%
“…The sequences of all constructs were confirmed by nucleotide sequencing, and protein expression from the constructs described in this study was confirmed following transfection by both immunofluorescence staining and Western immunoblotting. The general approach to generate a chimera with each type of cytoplasmic domain was to insert partial or full-length cDNA molecules into HindIII-XhoI or HindIII-XbaI restriction sites of the plasmid vector pCMV/IL-2R (22). This vector is driven by the CMV promoter, and it expresses the extracellular and transmembrane domains of the non-signaling ␣ subunit of the interleukin-2 receptor (IL-2R) as a fusion protein with any molecule of interest as the cytoplasmic domain, as illustrated in Fig.…”
Section: Construction Of Chimericmentioning
confidence: 99%